Evaluating the impact of an after-school program on overhand throwing and perceived motor competence among students from low socio-economic backgrounds in the U.S. - Albaloul, Omar; Nam, Kahyun; Kulinna, Pamela Hodges; Acri, Conner (Frontiers in Sports and Active Living, 2025)
The study examined the effect of a 5-week Comprehensive School Physical Activity Program (CSPAP) on overhand throw skills and perceived motor competence in students from low socio-economic backgrounds. Participants were children recruited from a Title 1 school in the Southwest U.S. Students were assigned to either CSPAP condition (n = 60, 26 boys, 34 girls; Mgrade = 4.27, SD = .43) or a control condition (n = 20, 7 boys, 13 girls; Mgrade = 4.00, SD = .35). Overhand throwing and perceived motor competence were assessed at baseline and post-intervention using the Test of Gross Motor Development—2nd Edition and Perceived Motor Competence for Children (PMC-C). The Analysis of Covariance test showed that students who participated in the CSPAP performed statistically significant improvements in the overhand throw compared to control students in the post-test p < .001, with a moderate effect size. However, there was no significant difference in the PMC-C score after the 5-week intervention between the CSPAP students and control students. CSPAP can improve overhand throwing in students from low-income families, but new strategies are needed to enhance perceived motor competence in after-school contexts.